Using text messaging to increase access to psychological intervention in adolescence: an exploration of the feasibility and effectiveness of the approach with young people in contact with the youth justice system. - Goodman, Karla (2018)
Introduction: This thesis seeks to explore the feasibility and effectiveness of using text messages (SMS) to improve psychological wellbeing amongst young people involved in the Youth Justice System. As this group are likely to be exposed to risk factors impacting on their psychological health, yet unlikely to access mainstream health services, the provision of alternative and accessible interventions for this group should be a key priority for service providers, commissioners and academics alike.